THE ROLE OF FOREIGN INVESTMENTS IN THE SOCIOECONOMIC DEVELOPMENT OF THE REGIONS - Khoshimov Sabir Murtazaevich (Scholar Express Journals, 2023)
The article discusses the role and importance of foreign investment in the socio-economic development of the regions of our republic, existing problems, analytical data, conclusions, suggestions and recommendations in this regard.
Keywords: investment attractiveness; foreign investment; infrastructure facilities